KAJIAN HUKUM TERHADAP PELAKSANAAN EKSEKUSI ANAK OLEH PENGADILAN AGAMA DALAM SUATU PUTUSAN PERCERAIAN - Rai Mantili (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2022)
Execution as a legal action taken by the court to the losing party in a case is a further rule and procedure of the case examination process. Execution or execution of a decision is an act carried out by force against the losing party in a case. Not all court decisions have executive power, not all court decisions can be executed. In a divorce case in the Religious Courts, if the judge has given a decision that one of the parties has been won as the holder of custody, then the party who must voluntarily hand over his custody rights to the winning party voluntarily. This is a lot in practice, often parties who do not want to give up custody of their children to the winning party. The results of this study indicate that the execution of child custody has two kinds of obstacles. The first obstacle is the "psychological obstacle of the child", because the child is not an object that can be executed and the second obstacle is a matter of cost, if the child is on the losing side but the losing party does not want to give up custody of the child to the winning party, who will will pay a fee if requesting the services of the police to force the child, because there is no state budget for the execution of child custody. Keywords: Divorce, religious courts, execution of children.